Experimental investigation of the variability in the dynamics of connected structures. (September 2016) - Souza, M R; Ferguson, N S
Abstract: Hydraulic pipes and cable bundles attached to host structures are widely found in engineering. This paper explores how variability in the connection points between structures affects the coupled dynamics. One at a time, two different one-dimensional waveguides are attached to a thin plate through a different set of point connections. Measurements considering randomly spaced connections were made and the experimental results are presented and compared to previously developed models. When multiples attachments are considered, the structure accommodates standing-like waves between the attachments, amplifying its response. It was possible to see the variability due the random spacing and, in a frequency-averaged sense, good agreement between the experimental data and the models were obtained. A comparison of the spatial response of the experiment and the infinite system is also presented.